Pedunculopontine nucleus deep brain stimulation produces sustained improvement in primary progressive freezing of gait. Issue 11 (22nd October 2010) - Wilcox, Robert A; Cole, Michael H; Wong, David; Coyne, Terry; Silburn, Peter; Kerr, Graham
Abstract : Objective: To assess the efficacy of bilateral pedunculopontine nucleus (PPN) deep brain stimulation (DBS) as a treatment for primary progressive freezing of gait (PPFG). Methods: A patient with PPFG underwent bilateral PPN-DBS and was followed clinically for over 14 months. Results: The PPFG patient exhibited a robust improvement in gait and posture following PPN-DBS. When PPN stimulation was deactivated, postural stability and gait skills declined to pre-DBS levels, and fluoro-2-deoxy-d -glucose positron emission tomography revealed hypoactive cerebellar and brainstem regions, which significantly normalised when PPN stimulation was reactivated. Conclusions: This case demonstrates that the advantages of PPN-DBS may not be limited to addressing freezing of gait (FOG) in idiopathic Parkinson's disease. The PPN may also be an effective DBS target to address other forms of central gait failure.